Does the regulatory quality matter in the relationship between climate finance and inclusive growth in Africa? - Isubalew Daba Ayana (PLoS ONE, 2026)
This study scrutinizes the effect of climate finance on inclusive growth in Africa. It further explores how regulatory quality dynamics impact the connection between climate finance and Africa’s inclusive growth. Grounded on panel macroeconomic data straddling 54 African states from 2013 to 2023 and employing the two-step system generalized method of moments (2SYS-GMM) econometric estimation technique, the subsequent outcomes appeared. First, climate finance encourages inclusive growth in Africa, while the interactive terms of climate finance and regulatory quality have a shrinking effect. Before interacting with the regulatory quality, a 1% in increase in climate finance heightened Africa’s inclusive growth by 0.3607% in the long run, while it was accompanying with a 0.1561% upsurge in the inclusive growth in the short run, all other factors remaining constant. Contrarily, the system GMM model publicized that in the long run, a one percent increase in the interactive terms of climate finance and regulatory quality of Africa signposts to a 0.775 percent diminution in inclusive growth, while it marks a 0.753 percent lessening in the short run, on average, and other things remaining constant. The study concludes that the feeble regulatory quality of Africa is harmful in both the long run and the short run. This suggests that negative regulatory quality dynamics completely shrink the positive effect of climate finance on the inclusive growth of Africa over the periods under this study. Further, the anticipated benefits of climate finance in fostering Africa’s inclusive growth may persist elusive unless noteworthy progresses are made to Africa’s currently existing regulatory frameworks.